Pengalaman Pertama Klien Terapi Bekam di Universitas Fort De Kock Bukittinggi - Putri, Lydia Mardison; Syukri, Rahmat (REAL in Nursing Journal, 2022)
Background: Improving the degree of health is mandatory as a human effort in business, in healthy life activities and illness are the determinants of achievement, when sick, treatment and care efforts have become a benchmark for activities, as well as health must be maintained in order to stay healthy and able to take active and passive prevention in order to achieve optimal health. In maintaining health, it can be done in a modern or traditional way, one of the traditional treatments is Cupping which has become a recommendation from the Prophet Muhammad, SAW. Methods: However, not many people are ready for this bekan action, so a study was conducted to determine the client's first experience of cupping therapy with a qualitative descriptive phenomenological approach with 13 participants, collecting data by interview and observation, and processing data analysis using Hubberman. Results: The results of the study were found to be traumatic invasive procedures, psychological responses, striving for health, which became the theme of the research results. Conclusion: It is recommended for health workers to provide education to the public that cupping can be used as an alternative therapy in improving health status with safe procedures and will not cause traumatic invasive procedures, so it is safe and comfortable to use.